2015
DOI: 10.1124/dmd.115.066829
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Oral Turinabol by Human Steroid Hormone-Synthesizing Cytochrome P450 Enzymes

Abstract: The human mitochondrial cytochrome P450 enzymes CYP11A1, CYP11B1, and CYP11B2 are involved in the biosynthesis of steroid hormones. CYP11A1 catalyzes the side-chain cleavage of cholesterol, and CYP11B1 and CYP11B2 catalyze the final steps in the biosynthesis of gluco-and mineralocorticoids, respectively. This study reveals their additional capability to metabolize the xenobiotic steroid oral turinabol (OT; 4-chlor-17b-hydroxy-17a-methylandrosta-1,4-dien-3-on), which is a common doping agent. By contrast, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…These authors wrote later in the text: "An additional controlled excretion study is needed to fully evaluate the time at which novel metabolites can be detected" [2]. In summary, it is clearly demonstrated that the detection window [11], has still seen these molecules except for authors. Again, authors stated that additional controlled excretion study is needed, but such study has not been conducted by any independent researcher and by WADA-accredited laboratories, since information of the results is not available anywhere.…”
Section: Allegation About Detection Window Of Novel Stable Metabolitesmentioning
confidence: 98%
See 1 more Smart Citation
“…These authors wrote later in the text: "An additional controlled excretion study is needed to fully evaluate the time at which novel metabolites can be detected" [2]. In summary, it is clearly demonstrated that the detection window [11], has still seen these molecules except for authors. Again, authors stated that additional controlled excretion study is needed, but such study has not been conducted by any independent researcher and by WADA-accredited laboratories, since information of the results is not available anywhere.…”
Section: Allegation About Detection Window Of Novel Stable Metabolitesmentioning
confidence: 98%
“…However, almost all newly discovered biological molecules are used to pass through several validation steps after their primary observation. In this respect, even authors of the established method [2] wrote in "Introduction" section of their manuscript following about previously studied "old" metabolites of turinabol: "In vitro metabolic experiments were also attempted which have shown that the incubation of DHCMT with human cytochrome P450 enzymes resulted in the formation of [11], but no one of the mentioned metabolites is related to those stated and proposed in 2012 year publication [2] and used by WADA-accredited laboratories. Among other findings, the authors concluded that "these findings suggest that steroidogenic cytochrome P450 enzymes can contribute to drug metabolism and should be considered in drug design and toxicity studies" [11].…”
Section: Time Elapsed From Discovering Of New Metabolites and Absencementioning
confidence: 99%
“…However, reducing the number of potential structures of steroid metabolites to be synthesized for analyte confirmation purposes is of considerable help and can be supported by the presented approach. Studies contributing to the understanding of routes of steroid metabolism and enzymes involved in respective processes were conducted with dehydrochloromethyltestosterone . Therefore, three steroidogenic cytochrome P450 enzymes (CYP11A1, CYP11B1, and CYP11B2) were produced, purified, and applied to in vitro studies with dehydrochloromethyltestosterone, which yielded a series of mono‐ and bishydroxylated species of the AAS.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Studies contributing to the understanding of routes of steroid metabolism and enzymes involved in respective processes were conducted with dehydrochloromethyltestosterone. [72] Therefore, three steroidogenic cytochrome P450 enzymes (CYP11A1, CYP11B1, and CYP11B2) were produced, purified, and applied to in vitro studies with dehydrochloromethyltestosterone, which yielded a series of mono-and bishydroxylated species of the AAS. These results indicate that the studied human cytochrome P450 enzymes can participate in AAS biotransformation, which was especially noteworthy regarding the hydroxylation of C-18 of dehydrochloromethyltestosterone, potentially contributing to the formation of the long-term metabolite denoted as 4-chloro-18nor-17β-hydroxymethyl,17α-methyl-5β-androst-13-en-3α-ol.…”
Section: Initial Testing Proceduresmetabolism Studies and New Target mentioning
confidence: 99%
“…These redox partners were chosen as they are well studied and characterized in detail. They serve as electron donors in vitro as well as in vivo to a range of bacterial and mammalian P450s, such as CYP106A2 23 , CYP106A1 24 , CYP105A1 25 , CYP109B1 26,27 , CYP267B1 28 , CYP264A1 29 , CYP11A1 30 , and CYP21A2 24,31 . The model substrate progesterone is a well-studied substrate of CYP106A2.…”
Section: Introductionmentioning
confidence: 99%